(untitled) (Journal of Forensic Medicine & Toxicology, 2026)
The aim of the study was to determine the mean values of cervico-incisal and mesio-distal odontometrics of maxil lary central incisors and maxillary canines among the Indian population; and investigate whether any significant sexual dimorphism (P value < 0.05) exists among them. The objective was also to discover the significant sexually dimorphic odontometric parameters in different age groups among the study population. Relationship of these odontometrics with the age of the subjects was also assessed. This cross-sectional study consisted of 104 subjects (54 males and 50 females). In each participant, cervico-incisal and mesio-distal odontometric dimensions of permanent maxillary central incisors and maxillary canines of both sides (CI11, MD11, CI21, MD21, CI13, MD13, CI23, MD23) were calculated intraorally, using a digital vernier caliper. Data obtained was then statistically analyzed using SPSS version 21.0. Six odontometric measurements were significantly greater in males than in females in the overall study population. CI23 emerged as the most reliable odontometric parameter. Specific significant odontometric parameters were also found in every age group among the study population. No significant relationship between any odontometric dimension and the age of participants was observed. It was revealed that the cervico-incisal odontometric measurements of maxillary central incisors and canines, and mesio-distal odontometric measurements of maxillary canines, can play a notable role in determining sex within the Indian population. Findings of this research can assist forensic odontologists in utilizing specific odon tometric parameters to ascertain the sex of individuals, when their age range is known and they are part of the Indian demographic.